Musimarch 2002. Causeries and Round Table Discussion: Chronicle of a Partially Imagined Event - Goldman, Jonathan (Circuit, 2002)
This article is at once a chronicle of the Musimarch festival and a reflection on certain aspects of the problematic of transcultural music, subject of the round table and causeries sessions that took place between composers and musicologists.